Social Entrepreneurship Model Based on Quadruple Helix Collaboration: Economic Empowerment in Disabilities Community: (Editorial Article) - Mulyaningsih, Hendrati Dwi (Journal of Social Entrepreneurship Theory and Practice, 2021)
Social entrepreneurship is a process of continuous innovation in classifying different social problems to overcome social problems and meet social needs. The social entrepreneurship approach is very promising in creating new opportunities for individuals with disabilities in the emerging industry. The conceptual contribution to developing a theory that explains the relationship between constructions has been less underlined. Thus, this study aims to identify different models and how they work and propose a conceptual model of social entrepreneurship to empower the economy in disability communities. This study uses descriptive analysis by conducting various literature syntheses to understand the contribution of entrepreneurship in social development. Based on discussion and analysis, new model propositions consider the value of co-creation stakeholders and supporting ecosystems such as academics, government, profit, and non-profit organizations and communities (quadruple helix concept). Overall, this study provides a conceptual framework that enables an understanding of the phenomenon of social entrepreneurship growth and its role in empowering community disabilities. Also, this research also tries to facilitate the stakeholders involved to contribute to the empowerment of community disabilities.